M28 Deferring treatment with pirfenidone results in loss of lung function that is not recovered by later treatment initiation. (15th November 2017) - Maher, T; Jouneau, S; Morrison, L; Lederer, D; Molina-Molina, M; Kirchgaessler, K-U; Gilberg, F; Axmann, J; Petzinger, U; Bendstrup, E
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) is characterised by a progressive loss of lung function. Intervention with an anti-fibrotic, such as pirfenidone, as early as possible in the disease course may be the most appropriate strategy to preserve lung capacity. 1 In this analysis, data from the pivotal CAPACITY (004/006; NCT00287716 /NCT00287729) trials and subsequent RECAP (012; NCT00662038 ) rollover trial were used to investigate the impact of deferring pirfenidone treatment on annual decline in lung function (forced vital capacity [FVC]) in patients with IPF. Methods: The annual rate of lung function (FVC; mL) decline was calculated for all treated patients who completed CAPACITY and RECAP. Weeks 0–120 included all patients randomised in CAPACITY to pirfenidone 2, 403 mg/day or placebo. Weeks 72–120 included data for the transition period, when patients either continued pirfenidone or switched to pirfenidone in RECAP. After Week 120, only data for patients in RECAP were included. Patients randomised to pirfenidone in CAPACITY were compared with those who received placebo in CAPACITY before initiating pirfenidone in RECAP. Results: From Week 0 to 120, the annual rate of lung function decline (FVC) was −142.0 mL (n=345) in patients who received pirfenidone in CAPACITY and −182.3 mL (n=347) in those who received placebo. During the transition period (Weeks 72–120), these values were −155.2 mL (n=236) and −151.9 mL (n=249) in patients who continued and switched to pirfenidone, respectively. In RECAP (≥Week 120), the annual rate of lung function decline in patients who received pirfenidone in both trials was −145.3 mL (n=219) and −140.9 mL (n=218) in those who switched from placebo to pirfenidone. Conclusions: These data show that loss of lung function during CAPACITY was not recovered during RECAP. Therefore, failure to initiate pirfenidone treatment in IPF as early as possible may lead to an irrecoverable loss of lung volume during the period without treatment. Funding: F. Hoffmann-La Roche, Ltd./Genentech, Inc. Reference: . Albera Cet al. Eur Respir J2016;48:843–851.